Effects of inspiratory muscle training in patients with obstructive sleep apnoea syndrome: a systematic review and meta-analysis - Javid Ahmad Dar; Aqsa Mujaddadi; Jamal Ali Moiz* (Sleep Science, 2022)
Obstructive sleep apnoea (OSA) is a common disorder marked by repetitive occurrence of breathing cessation during sleep due to partial or complete upper airway obstruction. An obstructive airway and the successive asphyxia chronically overload the inspiratory muscles resulting in an increased inspiratory effort. The present systematic review aimed to examine the effects of inspiratory muscle training (IMT) on inspiratory muscle strength [maximal inspiratory pressure (PImax)], severity of disease [apnea hypopnoea index (AHI)], sleep quality [Pittsburgh sleep quality index (PSQI)], day time sleepiness [Epworth sleepiness scale (ESS)], lung function [forced expiratory volume in 1 second (FEV1)] and exercise capacity [cardiopulmonary exercise testing, (CPET), 6 minute walk test, (6MWT)] in mild to severe OSA. Among 953 articles retrieved from various databases (PubMed, SCOPUS, Web of Science and Cochrane), 7 articles were found to be eligible for the present review. Randomized controlled trials reporting the effect of IMT in OSA were selected. The quality assessment was conducted using Cochrane risk-of-bias tool for randomized trials. All seven studies were meta-analyzed. The result depicted significant change in PImax, ES 1.73 (95%CI 0.54 to 2.92, p=0.004), PSQI -1.29 (95%CI -1.94 to -0.65, p<0.0001), ESS -1.08 (95% CI -1.79 to - 0.37, p=0.003) and FEV1 0.74 (95%CI 0.20 to 1.28, p=0.007). IMT may be considered as an effective treatment strategy in mild to severe OSA resulting in improved inspiratory muscle strength, sleep quality, daytime sleepiness, and lung function. However, there is still dearth evidence on repercussion of IMT on lung function and exercise capacity and warrants high quality evidence to reach definitive conclusions.